The Role of the National Narcotics Agency of Sukabumi Regency/City in Law Enforcement Against Narcotics Crimes in Sukabumi According to Undang-Undang Narkotika Number 35 of 2009 - Putri, Shayla; Kusumah, Haidan Angga (Dinasti Research, 2025)
The Role of the National Narcotics Agency of Sukabumi Regency/City in Law Enforcement Against Narcotics Crimes According to Undang-Undang Narkotika Number 35 of 2009. This study discusses the role of the National Narcotics Agency of Sukabumi Regency/City in law enforcement against narcotics crimes in accordance with Undang-Undang Narkotika Number 35 of 2009. The research aims to analyze the effectiveness and obstacles faced by the National Narcotics Agency of Sukabumi Regency/City in handling narcotics abuse and illicit trafficking. Using normative juridical and empirical juridical methods, data were collected through document studies and interviews with key informants. The results show that law enforcement efforts have not been optimal due to limitations in budget, authority, human resources, and legal framework. The study concludes that strengthening preventive measures, increasing the capacity of human resources, and optimizing coordination between law enforcement agencies are needed to improve the effectiveness of narcotics crime eradication in Sukabumi Regency/City.